Diseño de una plataforma informática para el almacenamiento y análisis de datos antropométricos. Antropos 2.0 (2008)
The tool Web ANTROPOS 2.0 developed for the managing of biometric information, it allows to generate statistical information of a studied population and to be consulted by any user been interested in the product design or spaces of works of reliable and effcient form, giving support and support to the academic and industrial community been interested in the development and construction of better living conditions.  This tool developed according to the engineering of the usability engineering from the accomplishment of three test that they allowed to understand the mental model of the user, then to check it (test explorative, comparative and of validation) and to obtain a comfortable, effcient and sure tool.